Solid state gas sensing - Comini, Elisabetta (Springer, 2017)
Solid State Gas Sensors offers insight into the principles, applications, and new trends in gas sensor technology. Developments in this field are rapidly advancing due to the recent and continuing impact of nanotechnology, and this book addresses the demand for small, reliable, inexpensive and portable systems for monitoring environmental concerns, indoor air quality, food quality, and many other specific applications. Working principles, including electrical, permittivity, field effect, electrochemical, optical, thermometric and mass (both quartz and cantilever types), are discussed, making the book valuable and accessible to a variety of researchers and engineers in the field of material science.